Blast-induced tinnitus and hyperactivity in the auditory cortex of rats. (6th January 2017) - Luo, Hao; Pace, Edward; Zhang, Jinsheng
Highlights: Blast induces delayed increases in spontaneous firing in the auditory cortex of rats with tinnitus. Blast induces delayed increases in bursting in the auditory cortex of rats with tinnitus. Blast-induced hyperactivity and increases in bursting in the auditory cortex may be related to chronic tinnitus. The results suggest that blast-induced hyperactivity in the brainstem is responsible for acute tinnitus. Abstract: Blast exposure can cause tinnitus and hearing impairment by damaging the auditory periphery and direct impact to the brain, which trigger neural plasticity in both auditory and non-auditory centers. However, the underlying neurophysiological mechanisms of blast-induced tinnitus are still unknown. In this study, we induced tinnitus in rats using blast exposure and investigated changes in spontaneous firing and bursting activity in the auditory cortex (AC) at one day, one month, and three months after blast exposure. Our results showed that spontaneous activity in the tinnitus-positive group began changing at one month after blast exposure, and manifested as robust hyperactivity at all frequency regions at three months after exposure. We also observed an increased bursting rate in the low-frequency region at one month after blast exposure and in all frequency regions at three months after exposure. Taken together, spontaneous firing and bursting activity in the AC played an important role in blast-induced chronic tinnitus as opposed to acute tinnitus, thus favoring a bottom-up mechanism.